(untitled) (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: This paper determined the microbial content of bed linens used by students based on period of usage, gender of user and types of fabrics. Design/Methodology/ Approach: Laboratory tests were conducted on bed linens used by students. Purposive and convenience sampling techniques were employed to select 32 each male and female participants living alone for the study. 32 pieces of bed linens, each 100% cotton and cotton/polyester blend, were used for the experiment. Two categories of gender (male and female) and two different periods of usage (one week and two weeks) were also employed. The statistical software employed to analyse the data collected was the Statistical Package and Service Solution (SPSS) for Windows version 26. Means and standard deviations of microbial load of bed linens were determined. Independent samples t-test and analysis of variance were employed to determine if differences existed between and among the variables studied. Findings: The study found no difference in microbial load in terms of duration and gender of the user. The results also showed more bacteria load on 100% cotton bed linen than on cotton and polyester blends. Research Limitation: The study’s sample was confined to a specific group of students at one university, limiting the generalizability of the findings to a broader student population or diverse living conditions. Practical Implication: The study’s outcome is significant for public health and daily hygiene practices. The Ghana health service can use the information to educate individuals on the dangers they will likely be exposed to using bed linens for an extended period without washing and raise awareness about the often-overlooked issue of microbial contamination in everyday environments. Social Implication: The study highlights the need for increased awareness and responsibility regarding personal hygiene within living environments. Originality/Value: This study advances the understanding of microbial contamination in students’ bed linens by identifying the roles of usage period, user gender, and fabric type.